The long winter - Wilder, Laura Ingalls 1867-1957; William,Garth (New York Harper & Row, 1968)
After an October blizzard, Laura's family moves from the claim shanty into town for the winter, a winter that an Indian has predicted will be seven months of bad weather.
Newbery Honor Award, 1941
Keywords: Frontier and pioneer life -- South Dakota -- Juvenile fiction; Families -- South Dakota -- Juvenile fiction; Blizzards -- Juvenile fiction; South Dakota -- Juvenile fiction